BELAJAR DENGAN DIALOG (Deep Dialog dan Critical Thiking Sebagai Model Penerapan Pendidikan Karakter) - Jefri Souhuwat (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
The caregivers of the Church Soya, in carrying out the sagat learning process, were accustomed to using monotonous lecture methods, the use of methods, strategies and learning media rarely seen in the learning process. This study aims to find out what the learning process is with the dialogue on Church Formal Education (PFG) for GPM Soya's. The data of this study were analyzed using qualitative research methods with data collection techniques are observation, interviews and literature and data analysis techniques are data reduction, display data and draw conclusions and verification. By using Deep Dialog and Critical Thiking Theory with dialogue methods in the learning process with results indicators are Silence, community building, concept discovery activities, reflection and evaluation.The results found in this study were that caregivers found it very difficult to use the method of dialogue with students, so the teaching and learning process carried out was very monotonous by using the lecture method. Children's creativity and caregivers are not honed and have no development. In-depth dialogue with children's goals and caregivers are open, honest, respectful of others and independent learning has not occurred in the learning process. These findings are analyzed by means of learning with silence in establishing internal and external dialogue, building a class community for democratic dialogue, finding concepts for independence in dialogue, reflection as an educational and evaluation dialogue as a means of achieving learning with dialogue.Keyword: Church Formal Dialogue and Education (PFG)